Ophiolite Obduction on Leti Island, as Described By Molengraaff and Brouwer (1915): Implications for Age and Genesis Of Metamorphic Complexes in the Outer Banda Arc, Eastern Indonesia - van Gorsel, J.T. (Ikatan Ahli Geologi Indonesia, 2012)
Geology, rocks and fossils of Leti Island, NE of Timor, were described in great detail by Molengraaff et al. (1915). Folded Early-Middle Permian sediments and basic volcanics in the south of the island gradually become low-grade metamorphics to the North, with further increases in metamorphic grade towards a serpentinite massif in the north of the island. In today's plate tectonic terms this may be characterized as 'ophiolite obduction', i.e. metamorphism of continental crustal material in a subduction zone. The serpentinite massif is overlain by Latest Oligocene shallow marine limestone with reworked clasts and detritus of serpentinite and metamorphic rocks. These observations suggest that the age of the metamorphic-ophiolite complex on Leti island is post-Early Permian (and is therefore not Australian continental crust basement) and younger than latest Oligocene (i.e. too old to represent metamorphism connected with the Late Neogene Banda arc- NW Australian continent collision).Metamorphic complexes on nearby Timor and on small islands to the East may all have a similar origin, despite the wide range of published radiometric ages and proposed tectonic models (from Precambrian Australian continental basement to 'the world's youngest blueschist belt'). Many complexes are associated with ophiolitic rocks, overlie imbricated Permian-Triassic sediments and are overlain by an Upper Cretaceous- Lower Miocene 'Banda Terrane' succession (not always complete) that includes tropical carbonates, arc volcanics and unconformities, very similar to that of the Sundaland margin. These broad similarities suggest all or most of the metamorphic complexes may be parts of a single 'Timor-Tanimbar' metamorphic belt of Cretaceous age.If this interpretation of a single, extensive Cretaceous-age collisional/ subduction zone complex is correct, it follows that (1) this could not have taken place along the NW Australia passive margin, where it is today, and (2) if Permian-Triassic sediments and volcanics are indeed the protoliths of all metamorphic complexes, a microplate carrying these 'Gondwana sequence' sediments must already have separated from the Gondwana margin, probably in Jurassic time. This leads us back to the tectonic scenario that was prevalent around 1980 (Barber (1978, 1981, etc.), which shows most of Timor as a microcontinental sliver that rifted off the Sundaland margin in the Tertiary (should be Late Miocene-Pliocene time) during slab rollback/arc splitting that opened the South Banda Sea. It returned microcontinental material that had rifted off the Gondwana margin in the Jurassic ('Gondwana sequence'), then collided with the Sundaland margin in the Cretaceous, after which it developed its overprint of Late Cretaceous- Early Miocene arc volcanics, tropical carbonates, etc.